2020
DOI: 10.15376/biores.15.1.1629-1640
|View full text |Cite
|
Sign up to set email alerts
|

Hydrochloric acid-catalyzed hydrothermal pretreatment of brown seaweed residues for enhancing biofuel production

Abstract: The hydrochloric acid-catalyzed hydrothermal pretreatment of brown seaweed residues (Laminaria japonica) was optimized with respect to three operating factors: temperature, time, and the concentration of HCl, using response surface methodology (RSM). In order to confirm the significance of the quadratic model, an analysis of variance was performed, which resulted in an F-value of 11.09. Therefore, the regression model was highly significant. Additionally, the pareto chart was used to contrast the absolute valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…From the economic standpoint of the macroalgal biorefinery, phycocolloids have frequently been the primary target for recovery due to being commercially valued [ 181 ]. Park et al [ 182 ] and Alfonsín et al [ 33 ] investigated the extraction of alginate and carrageenan, respectively, and assessed the appropriateness of the remaining residues as feedstock for rare sugar extraction using chemo-catalytic hydrolysis assay. Park et al [ 182 ] identified that 40% of alginate can be extracted from Laminaria japonica , and 107.5 g/L of glucose was successfully extricated post hydrochloric acid hydrolysis.…”
Section: Circular Biorefinery Approach- Microfluidic Mfc/bioplastic C...mentioning
confidence: 99%
See 1 more Smart Citation
“…From the economic standpoint of the macroalgal biorefinery, phycocolloids have frequently been the primary target for recovery due to being commercially valued [ 181 ]. Park et al [ 182 ] and Alfonsín et al [ 33 ] investigated the extraction of alginate and carrageenan, respectively, and assessed the appropriateness of the remaining residues as feedstock for rare sugar extraction using chemo-catalytic hydrolysis assay. Park et al [ 182 ] identified that 40% of alginate can be extracted from Laminaria japonica , and 107.5 g/L of glucose was successfully extricated post hydrochloric acid hydrolysis.…”
Section: Circular Biorefinery Approach- Microfluidic Mfc/bioplastic C...mentioning
confidence: 99%
“…Park et al [ 182 ] and Alfonsín et al [ 33 ] investigated the extraction of alginate and carrageenan, respectively, and assessed the appropriateness of the remaining residues as feedstock for rare sugar extraction using chemo-catalytic hydrolysis assay. Park et al [ 182 ] identified that 40% of alginate can be extracted from Laminaria japonica , and 107.5 g/L of glucose was successfully extricated post hydrochloric acid hydrolysis. Similarly, Alfonsín et al [ 33 ] suggested that a biorefinery approach using Eucheuma denticulatum for the production of carrageenan and rare sugars could be commercially viable and yielded 19.7% of extricated rare sugars corresponding to 0.30 g/L of glucose from the carrageenan-free residue through acid hydrolysis.…”
Section: Circular Biorefinery Approach- Microfluidic Mfc/bioplastic C...mentioning
confidence: 99%